2016
DOI: 10.1002/jor.23187
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of four sliding knots and three high‐strength sutures: Loop security is much different between each combination

Abstract: There are many types of sliding knots and suture materials used in arthroscopic surgery. The purposes of this study are (i) to evaluate the loop security of standard sliding knots when using different types of high-strength suture materials and (ii) to compare the loop security of a new sliding knot (Chula knot) to other standard sliding knots. Four configurations of sliding locking knots (Weston, SMC, Tennessee and Chula knots) were tied using three commonly used suture materials: MagnumWire, Hi-Fi, and Fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The literature has shown variation in knot strength to be a multifactorial phenomenon that is affected by both biomechanical factors such as suture material and knot configuration, as well as intrinsic variations in surgeon performance. Kuptniratsaikul et al 24 compared the loop security of the Weston, Chula, SMC, and Tennessee sliding knots using MagnumWire, Hi-Fi, and FiberWire sutures and found considerable variation in loop security across different knot-suture combinations. Similarly, Hassinger et al 25 found significant differences in loop security and knot security across 10 commonly used arthroscopic knots tied using the same suture material, suggesting that biomechanical factors such as knot type and suture material contribute to variation in knot strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has shown variation in knot strength to be a multifactorial phenomenon that is affected by both biomechanical factors such as suture material and knot configuration, as well as intrinsic variations in surgeon performance. Kuptniratsaikul et al 24 compared the loop security of the Weston, Chula, SMC, and Tennessee sliding knots using MagnumWire, Hi-Fi, and FiberWire sutures and found considerable variation in loop security across different knot-suture combinations. Similarly, Hassinger et al 25 found significant differences in loop security and knot security across 10 commonly used arthroscopic knots tied using the same suture material, suggesting that biomechanical factors such as knot type and suture material contribute to variation in knot strength.…”
Section: Discussionmentioning
confidence: 99%
“…Kuptniratsaikul et al. 24 compared the loop security of the Weston, Chula, SMC, and Tennessee sliding knots using MagnumWire, Hi-Fi, and FiberWire sutures and found considerable variation in loop security across different knot-suture combinations. Similarly, Hassinger et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study included surgical interventions for the treatment of shoulder instability and rotator cuff tears, but techniques and indications for these surgical procedures also vary and are not directly comparable across studies. It should be noted, however, that there are studies 27,30 that suggest that as long as 3 reversing half-hitch knots are tied, the strength of the SK is dependent on the half-hitch throws and independent of SK configuration. Additionally, the suture material and number of reversing half-hitches on alternating posts locking the knot in position affect the amount of friction holding the knot in position and, therefore, the integrity of the knot itself.…”
Section: Discussionmentioning
confidence: 99%
“…The number of labral penetrations with the BirdBeak suture passer must be no more than 1 or 2; otherwise, large labral defect will be created. Knot tying is done using a Chula Knot, 22 followed by 3 reversing half-hitches through the posterior portal. Excess suture limbs are cut arthroscopically.…”
Section: Surgical Techniquementioning
confidence: 99%